Construction of plant transformation vector to contain metroxylon sagu alcohol dehydrogenase 1 - Kon, Iris Chu Lin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Alcohol dehydrogenase (ADH) is the critical enzyme responsible for the fermentative metabolism in plants especially under abiotic stress conditions. The levels of expression of Adh could be different in respective parts of plant in individual species. In this study, E. coli harbouring pET41(a)+msAdhl was used as the source to isolate the msAdhl gene through alkaline lysis method in order to be ligated into pGSAI131 to produce a plant transformation vector. The conserved region of msAdhl of 1.1 kb was amplified through PCR by using primer set of 5' Ndel-adh and 3'_msAdhl-Xhol. The msAdhl fragments with the concentration of 64.81 ng/Ill were restricted with Nde I and Xho I to remove the 3'-terminal adenines. Restriction digestion was performed on pGSAI131 at Nco I site to obtain linearized plasmid. The staggered ends of both the insert fragments and the linearized pGSAll31 were blunted by using T4 DNA Polymerase. The insert was ligated into pGSAll31 using T4 DNA Ligase before transformed into E. coli XLI Blue though heat-shock method. The verification of successfully constructed plasmids with correct orientation of msAdhl was performed via Colony PCR and sent for sequencing.